Location based services of nearest petrol station using asymmetric key algorithm / Muhammad Awwab Mohd Amdan - Mohd Amdan, Muhammad Awwab (2014)
Location-based applications enabled by advances in sensing and tracking technology but it also create significant privacy risks. Anonymity can provide a high degree of privacy; reduce the service providers' requirements for safeguarding private information and save service users from dealing with service providers' privacy policies. Guaranteeing anonymous usage of location-based services however requires that the precise location information transmitted by a user cannot be easily used to identify the subject. In this paper, asymmetric key algorithm is used. Asymmetric key algorithm is also known as public-key cryptography, is a class of cryptographic algorithms with require two separate keys, one is secret (private) key and another one is public key. El-gamal encryption system is an asymmetric key encryption algorithm which is based on the Diffie-Hellman key exchange. The target petrol station location of longitude/latitude is determined firstly. The coordinate is incorporated with a random key for data encryption. Users only can detect the location by decrypting the El-Gamal encryption.